The Urgency to Adopt Victim Impact Statement in the Indonesian Criminal Justice System - Ali, Mahrus; Nurhidayat, Syarif (KnE Social Sciences, 2023)
This study is aimed to examine the need for adopting a Victim Impact Statement in the Indonesian criminal justice system. Due to the absence of Indonesian law that acknowledges the victims’ right to express opinions that directly affect them prior to a panel of judges imposing a punishment, this adoption is necessary. This paper employed doctrinal legal research that mainly focused on the Code of Criminal Procedure provisions supported by secondary legal sources. The results showed that VIS was the statements made by someone who has lost something because of a crime or another painful occurrence. The content of the information indicated the psychic, emotional, psychological, or financial consequences of a crime suffered/experienced by the victim or their family. Several advantages were found in the VIS, including giving victims a formal role in the criminal justice system and raising victim satisfaction with the criminal justice system. As they allow victims to share their stories before the court’s ruling, some of these advantages are essential for Indonesia’s integration of VIS into its criminal justice system. Hence, the legislatures are suggested to adopt VIS in the Criminal Procedure Code and other sectoral legislation. Keywords: Victim Impact Statement, Criminal Justice System, Proportionality, Prevention